2019
DOI: 10.1002/jgm.3066
|View full text |Cite
|
Sign up to set email alerts
|

P2RY12:rs7637803 TT variant genotype increases coronary artery aneurysm risk in Kawasaki disease in a southern Chinese population

Abstract: Background Activated‐platelet increases the risk of thrombosis in Kawasaki disease (KD) patients with a coronary artery aneurysm (CAA). The ADP pathway is one of the platelet activation and aggregation pathways. The P2RY12 gene encodes the ADP receptor that is highly concentrated on platelets. However, few studies have reported on P2RY12 in relation to KD susceptibility with or without CAA. Methods We recruited 1335 healthy controls and 776 KD patients, including 103 with CAA, and selected five P2RY12 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
4
7
0
Order By: Relevance
“…Many studies have shown that P2RY12 may be a protective factor for clopidogrel and aspirin resistance [19,20]. As we described previously [21], the P2RY12: rs7637803 TT variant genotype increased the risk of coronary artery aneurysm in KD patients in a southern Chinese population. However, no studies have focused on the connection between the P2RY12 polymorphism and IVIG resistance in KD.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…Many studies have shown that P2RY12 may be a protective factor for clopidogrel and aspirin resistance [19,20]. As we described previously [21], the P2RY12: rs7637803 TT variant genotype increased the risk of coronary artery aneurysm in KD patients in a southern Chinese population. However, no studies have focused on the connection between the P2RY12 polymorphism and IVIG resistance in KD.…”
Section: Introductionsupporting
confidence: 62%
“…However, because the five SNPs in the P2RY12 gene are associated with aspirin and clopidogrel resistance, based on this background, we investigated whether the five SNPS were a relationship between P2RY12 polymorphisms and IVIG resistance in KD patients. A previous study by our research group focused on the relationship between P2RY12 polymorphism with KD genetic susceptibility and coronary artery aneurysm (CAA) complications [21]. e study found that rs7637803 significantly increased CAA risk in KD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing evidence that genetic polymorphisms are important determinants of CAAs in KD, which could result in predispositions to adverse outcomes [ 29 31 ]. However, there is less evidence about the relation between platelet receptor gene polymorphisms and KD, especially coronary artery abnormality.…”
Section: Discussionmentioning
confidence: 99%